Apropriação das tecnologias de informação e comunicação pelos gestores educacionais - Borges, Marilene Andrade Ferreira (2009)
The objective of this thesis is to investigate how people Appropriate digital technologies, more specifically, to reveal and to understand how this process takes place. Initially the use of the term Appropriation was studied in different knowledge areas.The practical work included the study of the training course "Projeto Gestão Escolar e Tecnologias" (School and Technologies Management Project) and the data used was the text extracts from the "Memoriais Reflexivos" (Reflexive Memorials) produced by educational managers who participated in the course. These extracts were analyzed, categorized, compiled and submitted to a new analysis, using a multidimensional statistical method performed by the software CHIC- Coercion, Implication and Hierarchic Classification. The software generated similarity trees and the numbers of occurrences of the specified categories. Bar charts were then elaborated based on these numbers,using Excel. Based upon the analysis of all this information the result showed that: the presence of orientation principles of the Complex Thought, indicating that the process of technological Appropriation is a Complex process; the relations established among the person, the object and the "other", signaling that technological Appropriation is not in the person nor in the technologies itself, but it is in the relations established among them; and the Appropriation is configured as a spiral in an ascending movement, which happens as part of the computer mediation, peers and the course professors. This confirms, therefore, that the digital technologies Appropriation is a Relational, Complex and Spiral process, which is constituted in levels, although singular in its identities, they are part of a unique movement. At the base of this process it is the Emotional level which supports the existence of other levels such as Imitation,, Relation- Communication, Relation-Information, Reflective-Relation/Expression and Selfeducation. The Emotional level is not related to the Technical-Operational level. The identification, the comprehension and the understanding of these levels, will be able to contribute to the educators' training actions or to other segments that have digital technologies as one of the supports for its accomplishment, to use these technologies as communication, information and expression means, allowing the students to appropriate them. Another result is to extend to the persons who have not appropriated the technologies, but who are trying to look for means to the realization of their emotions (MATURANA, 2001)